Expanding the reaction space of aldolases using hydroxypyruvate as a nucleophilic substrate. Issue 2 (2nd December 2016) - de Berardinis, Véronique; Guérard-Hélaine, Christine; Darii, Ekaterina; Bastard, Karine; Hélaine, Virgil; Mariage, Aline; Petit, Jean-Louis; Poupard, Nicolas; Sánchez-Moreno, Israel; Stam, Mark; Gefflaut, Thierry; Salanoubat, Marcel; et al.
Abstract : Hydroxypyruvate was shown to be a nucleophile for class II pyruvate aldolases isolated from biodiversity, allowing unprecedented stereoselective cross-aldol reactions. Abstract : Aldolases are key biocatalysts for stereoselective C–C bond formation allowing access to polyoxygenated chiral units through direct, efficient, and sustainable synthetic processes. The aldol reaction involving unprotected hydroxypyruvate and an aldehyde offers access to valuable polyhydroxy-α-keto acids. However, this undescribed aldolisation is highly challenging, especially regarding stereoselectivity. This reaction was explored using, as biocatalysts, a collection of aldolases selected from biodiversity. Several enzymes that belong to the same pyruvate aldolase Pfam family (PF03328) were found to produce the desired hexulosonic acids from hydroxypyruvate andd -glyceraldehyde with complementary stereoselectivities. One of them was selected for the proof of concept as a biocatalytic tool to prepare five (3 S, 4 S ) aldol adducts through an eco-friendly process.